Pengaruh E-Commerce dan Sistem Informasi Akuntansi dalam Pengambilan Keputusan untuk Berwirausaha” (Studi Empiris pada Mahasiswa Akuntansi Fakultas Ekonomi dan Bisnis Universitas Nusa Nipa Maumere) - Nurak, Yuliana Novia; Pipiet Niken Aurelia; Yoseph Darius Purnama Rangga (Jurnal Projemen UNIPA, 2026)
This research aims to determine the influence of e-commerce and accounting information systems (AIS) on entrepreneurial decision making among accounting students at the economics and business faculty, Nusa Nipa University, Maumere. The type of research used is quantitative research. This research data method uses primary data which means the respondents' answers to the questionnaire statements distributed and then measured using a Likert scale. The total sample was 38 accounting student respondents. The data collection technique is by distributing questionnaires using Google Forms which have been tested for validity and reliability, multiple linear regression analysis tests, hypothesis testing via the t test and f test, as well as the coefficient of determination (R2). In processing the data using SPSS version 23. Based on the research results, E-Commerce has a positive and significant effect on Decision Making for Entrepreneurship, the Accounting Information System has a positive and significant effect on Decision Making for Entrepreneurship, E-Commerce and the Accounting Information System together have a positive effect on Decision Making for Entrepreneurship.